Camp in Pravieniškės near Kaunas in 1941–1944 - Tomkiewicz, Monika (Genocidas ir rezistencija, 2023)
The camp in Pravieniškės was located within the administrative boundaries of Pravieniškės, located about 25 km from Kaunas. It was established during the period of the Republic of Lithuania, as a correctional facility. In August 1941 the Germans established the Pravieniškės Transitional Labour Camp (Zwangsarbeitslager Provenischken) there, which from 1943 was a branch of the Kaunas Concentration Camp (KL Kaunas) and continued to serve as a labour camp. Detainees were brought to this camp from the prisons of the General Commissariat of Lithuania, i.e. the Lukiszki Prison in Vilnius, the Kaunas Prison and Ponevezh (Panevėžys). People of various nationalities were held in Pravieniškės (Prawieniszki): Lithuanians (60%), Poles, Russians, Roma and Jews (mainly from the Kaunas ghetto). About 1,000 prisoners could be held in this camp at a time. People were sent here for a variety of offences: political prisoners, violators of forced labour orders, Soviet prisoners of war with their families, and those convicted of common crimes. Also incarcerated in Pravieniškės by administrative decision were deserters from the German army convicted of evading military service in the German army. People of Polish nationality placed in Pravieniškės were mainly accused of belonging to the resistance movement, communist activity, listening to the radio, possession of weapons, sabotage, escape from forced labour and communist activity. Guards executed prisoners on the camp grounds and in nearby forests. About 280 Jews were shot there in August 1941, and another 253 Jews in September 1941. Also, many attempts to escape from the camp were punished by execution. As the Eastern Front approached the borders of the Reich, the process of obliterating the traces of the crimes committed began. Due to the relatively small number of those murdered, it was not necessary for the notorious Sonderkommando 1005 to arrive in the area. A few dozen men directed to burn the corpses of those murdered in the nearby forest were enough. Members of the Pravieniškės camp crew were tried after the war by various organs of the Soviet justice system: courts, tribunals and collegia. Also in Poland, at the Institute of National Remembrance in Gdansk, an investigation was conducted into the case. Beginning in mid-July 1944, people convicted by Soviet tribunals were incarcerated in the camp in Pravieniškės: former camp guards, as well as members of the Vilnius Home Army arrested after Operation ‘Ostra Brama’. The prisoners were again employed to work on the peat bog and in the camp greenhouse. Today, every Lithuanian associates the name of Pravieniškės with the prison. A penitentiary facility still operates on the site of the former camp with places for 2,500 inmates, including those sentenced to life imprisonment.